Control of chromium dopant content in optical ceramics Cr:YAG - Gayduk, O.V. (Functional Materials, 2017)
Spectrophotometric determination of chromium in the presence of predominating yttrium and aluminum quantities was investigated by the method based on the reaction Cr(VI) with diphenylcarbazide. The optimum conditions of Cr(III) oxidation by potassium permanganate were established. A spectrophotometric technique for determination of 0.005-0.3 % of chromium in Cr-doped yttrium aluminum garnet ceramics was developed. The determination error is 1-5 %.